What do banks lose money on during crises? - Kasper Kragh-Sørensen; Haakon Solheim (Norges Bank, 2014)
We look at a wide range of national and international crises to identify banks' exposures to losses during banking crises. We find that banks generally sustain greater losses on corporate loans than on household loans. Even after sharp falls in house prices, losses on household loans were often moderate. The most prominent exception is the losses incurred in US banks during the 2008 financial crisis. In most of the crises we study, the main cause of bank losses appears to have been property-related corporate lending, particularly commercial property loans. In a box, we also summarise characteristics of developments in the banking industry ahead of banking crises.
hdl:11250/2998632
Keywords: 330